Cutaneous Lymphoma at Injection Sites: Pathological, Immunophenotypical, and Molecular Characterization in 17 Cats. (July 2016) - Roccabianca, P.; Avallone, G.; Rodriguez, A.; Crippa, L.; Lepri, E.; Giudice, C.; Caniatti, M.; Moore, P. F.; Affolter, V. K.
Feline primary cutaneous lymphomas (FPCLs) account for 0.2% to 3% of all lymphomas in cats and are more frequently dermal nonepitheliotropic small T-cell tumors. Emergence of FPCL seems unrelated to feline leukemia virus (FeLV) serological positivity or to skin inflammation. A total of 17 cutaneous lymphomas with a history of vaccine injection at the site of tumor development were selected from 47 FPCLs. Clinical presentation, histology, immunophenotype, FeLV p27 and gp70 expression, and clonality were assessed. A majority of male (12/17), domestic short-haired (13/17) cats with a mean age of 11.3 years was reported. Postinjection time of development ranged from 15 days to approximately 9 years in 5 cats. At diagnosis, 11 of 17 cats had no evidence of internal disease. Lymphomas developed in interscapular (8/17), thoracic (8/17), and flank (1/17) cutaneous regions; lacked epitheliotropism; and were characterized by necrosis (16/17), angiocentricity (13/17), angioinvasion (9/17), angiodestruction (8/17), and peripheral inflammation composed of lymphoid aggregates (14/17). FeLV gp70 and/or p27 proteins were expressed in 10 of 17 tumors. By means of World Health Organization classification, immunophenotype, and clonality, the lesions were categorized as large B-cell lymphoma (11/17), anaplastic large T-cell lymphoma (3/17), natural killer cell–like (1/17) lymphoma, or peripheral T-cell lymphoma (1/17). Lineage remained uncertain in 1 case. Cutaneous lymphomas at injection sites (CLIS) shared some clinical and pathological features with feline injection site sarcomas and with lymphomas developing in the setting of subacute to chronic inflammation reported in human beings. Persistent inflammation induced by the injection and by reactivation of FeLV expression may have contributed to emergence of CLIS.